1996 Olympic Games in Atlanta: The best female volleyball-teams: Brazil - Fröhner, B.; Zimmermann, B. (The Coach, 1997)
In the preliminaries Brazil beat both Cuba and Russia 3:0 thus becoming the favourite for the Olympic title. Despite of changes in the team (Caldeira got injured, Alvarez did not belong to the initial line-up) the Brazilian team showed a playing style which generally is considered to be a landmark for future women's international top volleyball. The play combines serve reception accuracy and flexible, highly efficient defence behaviour, similar to the Chinese team, with offensive blocking (three-players-block), hard and varying attacks, which can be compared with Cuba's attacking power, exemplary combination play with the incorporation of back row attacks and powerful service tactics with a systematic incorporation of jumping spike services (two players). Though we found a certain rationalisation compared with 1994 in this physically very demanding, variable and quick attacking play (power volleyball) the team had again to pay its athletic tribute during Olympic tournament with eight matches (defeat against Cuba, a very close victory against Russia at the end of the tournament).